EXTH-73. HETEROGENEITY IN CELL SURFACE ANTIGEN AND HLA CLASS I EXPRESSION IN PEDIATRIC BRAIN TUMORS AND ITS IMPACT ON T-CELL IMMUNOTHERAPY. (9th November 2020) - Houke, Haley; Zhu, Xiaoyan; Mercer, Kimberly S; Stripay, Jennifer L; Chiang, Jason; Baker, Suzanne; Roussel, Martine F; Gottschalk, Stephen; Krenciute, Giedre
Abstract: Immunotherapy with tumor antigen-specific chimeric antigen receptor (CAR) and/or ab (T-cell receptor) TCR T-cells has the potential to improve clinical outcomes of patients with pediatric brain tumors. As a prerequisite for successful T-cell therapies, we must determine which cell surface antigens are expressed and targetable in these tumors, and if HLA Class I is present, which is necessary for ab TCR T-cell recognition. Therefore, in this study we systematically analyzed pediatric patient-derived orthotopic xenograft (PDOX) brain tumor samples for cell surface expression of five known CAR targets: IL13Ra2, HER2, EphA2, B7-H3, and GD2, as well as HLA Class I. We established and validated a flow cytometry-based method of profiling tumor-associated antigens. Fifty-three PDOX samples have been profiled to date, including medulloblastoma, high grade glioma (HGG), diffuse intrinsic pontine glioma (DIPG), atypical teratoid rhabdoid tumor (ATRT), and ependymoma, among others. Our results showed high variability within and between individual samples. B7-H3 was the most consistently expressed, seen in 98% of the samples tested. We validated these results by conventional immunohistochemistry staining for B7-H3 and found comparable RESULTS: HLA Class I was highly expressed on all HGG samples but was undetectable on 47.8% of other brain tumor samples. This suggests that down-regulation of HLA class I is one mechanism by which brain tumors evade conventional T-cells, and that HLA-independent CAR T-cells would be useful therapies. We also compared expression of antigens in fresh patient samples and corresponding PDOX tumors and saw that they were indeed similar. To our knowledge, this is the largest group of pediatric brain tumor PDOX samples methodically analyzed for potential CAR target antigens and HLA Class I. Taken together, our data demonstrate that elimination of tumors by CAR T-cell immunotherapies will require targeting multiple antigens, and our profiling method could inform how to circumvent antigen-negative relapse.